PERENCANAAN BANGUNAN GEDUNG SUPERMARKET KABUPATEN BOYOLALI - Kurniawan, Muhamad; Sasi, Windu; Hartopo, Hartopo; Apriyanto, Totok (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
Boyolali is a developing district in Central Java Province. Therefore, many people from outside the area come to Boyolali to do business or develop their businesses. In order for the activities carried out to run well, adequate and supportive facilities are needed, so the construction of a Supermarket Building is planned. The structural planning for the Boyolali district supermarket building is in Siswodipuran, Boyolali District, Boyolali Regency, Central Java. This supermarket building was built to improve MSMEs for people in Boyolali.This building planning was carried out using primary data, such as soil survey data, and supplemented with other secondary data. This structural planning analysis is assisted by the SAP2000 software application for structural modeling and calculating internal forces. The analysis carried out includes: calculation of the roof structure, beams, columns and foundations.From the analysis results, it was obtained that the roof rafter beam was IWF 300.150.6,5.9, CNP purlins 150.50.20.2.3, steel columns IWF 300.150.6,9.9. Block sizes vary from 40x80 cm, 35x70, 30x60, 25x50, blocks measuring 25x40 and 20x30. Column sizes 80x80 cm, 70x70 cm, 60x60 cm. The foundation uses bored piles F2: 1.20x2.20x1.10 m with 2 bored piles measuring 60x60 cm, depth 5.5 m, F4: 2.20x2.20x1.40 m with 4 bored piles measuring 60x60 cm, depth 5.5 m, F6: 2.20x3.20x1.55 m with 6 bored piles measuring 60x60 cm, depth 5.5 m, F8: 2.20x4.20x2.00 m with 8 bored piles measuring 60x60 cm, depth 5.5 m. From the results, each structural element of the building can be categorized as safe.